1) Wykonaj redukcję wyrazów podobnyh :
a) x + y + x + y + x + y - x - y =
b) x² - y + x - y - x² - x² + x =
c) 3x - 2y + 5x - 6y - x =
d) 8x - (4x + 6y - 5) - (-5y + 8x - 2) =
e) (2a + b) - (3a + 6b - 1) + a + 4b =
f) - (x² - 2xy) - (xy - 2x² + 4) + 3xy - x² =


2) Doprowadź do najprostszej postaci :
a) 6a - (2a - 3b) + (a - 6b) =
b) - (2 - 5x) + (1 - 4x) - x =
c) (a - b) + (3a + 2b) - (4a - 3b) =
d) - (3x - 4y) - (2x - 3y) + (- y + 4x) =
e) (ax² + ax - a - x) - (2ax - 3ax² + a - x) + (2a - ax²) =
Proszę odpowiedzcie mi :*

3

Odpowiedzi

2010-01-29T22:01:04+01:00
A)
2x+2y
b)
-x²+2x-2y
c)
7x-8y
d)
-4x-y+7
e)
-b+1
zad 2
a)5a- 3b
b)-1
c)-2b
d)-x+6y
e)3ax²+3ax
2010-01-29T22:03:57+01:00
A) 2x+2y
b)2x-2y -x²
c)7x-8y
d)9x-6y-7
e)1-b
f)6xy-4+2x²

zad 2.
a)5a-3b
b)-1
c)4b
d)x+6y
e)3ax² -x
  • Użytkownik Zadane
2010-01-29T22:04:20+01:00
1.
a) x + y + x + y + x + y - x - y = = 2x +2y
b) x² - y + x - y - x² - x² + x = -x² - 2y + 2x
c) 3x - 2y + 5x - 6y - x = 7x - 8y
d) 8x - (4x + 6y - 5) - (-5y + 8x - 2) = 8x - 4x - 6y + 5 +5y - 8x + 2 = -4x - y + 7
e) (2a + b) - (3a + 6b - 1) + a + 4b = 2a + b - 3a - 6b + 1 + a + 4b = -b +1
f) - (x² - 2xy) - (xy - 2x² + 4) + 3xy - x² = -x² +2xy - xy + 2x² - 4 + 3xy - x² = 4xy - 4

2.
a) 6a - (2a - 3b) + (a - 6b) = 6a - 2a + 3b + a - 6b = 5a - 3b
b) - (2 - 5x) + (1 - 4x) - x = -2 + 5x + 1 - 4x - x = -1
c) (a - b) + (3a + 2b) - (4a - 3b) = a - b + 3a + 2b - 4a + 3b = 4b
d) - (3x - 4y) - (2x - 3y) + (- y + 4x) = - 3x + 4y - 2x + 3y - y + 4x = -x + 6y
e) (ax² + ax - a - x) - (2ax - 3ax² + a - x) + (2a - ax²) = ax² + ax - a - x -2ax + 3ax² - a + x + 2a - ax² = 3ax² - ax
1 5 1